Vaccine Hesitancy and Cognitive Biases: A tailored approach for a better communication. (20th October 2021) - Casigliani, V; Menicagli, D; Fornili, M; Lippi, V; Chinelli, A; Stacchini, L; Baglietto, L; Lopalco, PL; Tavoschi, L
Abstract: Background: Vaccine hesitancy (VH) remains worldwide a reason of concern. Most of the vaccination education strategies followed a 'fact-based' approach, based on the assumption that decision making is a rational process, without considering the influence of cognitive biases and heuristics. Our study aimed at identifying factors involved in the parents' vaccination choice to inform and shape communication interventions. Methods: We conducted an online national survey among parents between November 2020 and April 2021. The questionnaire consisted of 59 items organised in 5 parts: personal information, cognitive biases, risk aversion, conspiracy mentality, and VH. Exploratory factor analysis was conducted to identify latent variables underlying the 19 items related to the 6 cognitive biases. Factors were categorised in quintiles and the corresponding pseudo-continuous variables used as predictors of the VH. Logistic regression model was applied to assess the association of the VH with factors, conspiracy mentality and risk propension. We adjusted for age, gender, economic status, and education levels. Results: The study included 939 parents, 764 women (81.4%), 69.8% had a degree or higher level of education. Considering cognitive biases, four factors explaining 54% of the total variance were identified and characterised as: fear of the side effects of vaccines (scepticism factor); carelessness of the risk and consequences of infections (denial factor); optimistic attitude (optimistic bias factor); preference for natural products (naturalness bias factor). All factors were positively associated with VH (p < 0.001) as were conspiracy mentality (p = 0.007) and risk propension (p = 0.002). Conclusions: This study confirmed the need to amplify the model used to analyse the VH considering cognitive biases as an important factor affecting the parents' decision making. These results may be useful to design personalised communication interventions regarding vaccines and vaccination. Key messages: The model used to analyse the vaccine hesitancy needs to be extended including the evaluation of cognitive biases and heuristics. Communication interventions to promote vaccine acceptance should be tailored and personalized on the basis of the drivers of choice of the parents.